New molecular packing in a crystal of pseudoazurin from Alcaligenes faecalis: a double‐helical arrangement of blue copper. Issue 3 (1st March 2017) - Fukuda, Yohta; Mizohata, Eiichi; Inoue, Tsuyoshi
Abstract : A new molecular packing of pseudoazurin from A. faecalis shows a right‐handed double helix composed of blue copper sites. Abstract : Pseudoazurin from the denitrifying bacterium Alcaligenes faecalis ( Af PAz) is a blue copper protein and functions as an electron donor to copper‐containing nitrite reductase (CuNIR). Conventionally, Af PAz has been crystallized using highly concentrated ammonium sulfate as a precipitant. Here, a needle‐like crystal of Af PAz grown in a solution containing a macromolecular precipitant, polyethylene glycol 8000 (PEG 8000), is reported. The crystal belonged to space group P 61, with unit‐cell parameters a = b = 68.7, c = 94.2 Å. The structure has been determined and refined at 2.6 Å resolution. The asymmetric unit contained two Af PAz molecules contacting each other on negatively charged surfaces. The molecular packing of the crystal showed a right‐handed double‐helical arrangement of Af PAz molecules and hence of blue copper sites. This structure provides insight into the excluded‐volume effect of PEG and the manner of assembly of Af PAz.